Return to on-snow performance in ski racing after anterior cruciate ligament reconstruction - Morris, N.; da Silva Torres, R.; Heard, M.; Baker, P. D.; Herzog, W.; Jordan, M. J. (The American Journal of Sports Medicine, 2025)
Background: The individual variation in on-snow performance outcomes after anterior cruciate ligament (ACL) reconstruction (ACLR) in elite alpine ski racers has not been reported and may be influenced by specific injury characteristics.